(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study aimed to evaluate the efficacy of Intracanal calcium hydroxide removal with different techniques. Materials and methods: Seventy-five freshly extracted, non-carious, single canalled lower first premolars, having anatomic characteristics similar to each other, extracted for the orthodontic purpose were collected. After the root canal preparation, Calcium hydroxide was placed into the working length using lentulo spiral instrument till the medicament was visible at the apex. The specimens were segregated into three groups; Group 1: Rotary Files, Group 2: EndoVac system and Group 3: Ultrasonics. The evaluation was done with SEM in the coronal and apical third of the roots with a magnification of 1000x. The statistical analysis was done using statistical packages for social sciences (SPSS) software, version 20.0 for Windows (SPSS Inc., Chicago, IL). A p-value of less than 0.5 was considered significant statistically. Results: Maximum removal of Ca(OH)2 was analyzed in the EndoVac system (2.90 ± 0.12) followed by the rotary files (1.76 ± 0.26) and least was seen with Ultrasonics (1.32 ± 0.14). The p-value of 0.001 was seen between the coronal and apical third with the EndoVac system which is statistically significant. The significant difference statistically was observed between Rotary Files vs. Ultrasonics at apical third and with the EndoVac system vs. Ultrasonics at coronal third as well as at the apical third with p-value 0.001. Conclusion: It can be concluded that the EndoVac technique was effective in removing Ca(OH)2 medicament from the coronal and apical third of the root canal significantly. Clinical significance: Calcium hydroxide removal before the obturation was of priority as the Ca(OH)2 remnants have a negative impact of the ability for sealing the obturation mate- rial. Therefore, having a complete knowledge regarding the effective technique is much important.